Twofold pictorial experience, propositional imagining and recognitional concepts: a critique of Walton’s visual make-believe - Arienti, Marco (Phenomenology and Mind, 2018)
Kendall Walton has defined pictorial experience as a visual game of make-believe, which consists in imagining our actual seeing the representational prop to be a fictional face to face seeing the represented subject. To maintain a twofold awareness of these two visual aspects while avoiding a phenomenal clash between them, Walton needs to characterise visual make-believe as involving a propositional imagining. Unfortunately, the strategy does not seem to be successful. Whether propositional imagination is taken as a simple descriptive report or as conceptually penetrating our perception, Walton’s account is not able to secure the visual and the twofold character of pictorial recognition.